Financial Deepening, Inequality, and Growth : A Model-Based Quantitative Evaluation - Townsend, Robert (IMF Working Papers; Working Paper, 2003)
We propose a coherent unified approach to the study of the linkages among economic growth, financial structure, and inequality, bringing together disparate theoretical and empirical literature. That is, we show how to conduct model-based quantitative research on transitional paths. With analytical and numerical methods, we calibrate and make tractable a prototype canonical model and take it to an application, namely, Thailand 1976-1996, an emerging economy in a phase of economic expansion with uneven financial deepening and increasing inequality. We broadly replicate the actual data, test the model formally, and identify anomalies.